Macrophage-induced reactive oxygen species in the initiation of pancreatic cancer: a mini-review - Döppler, Heike R.; Storz, Peter (Frontiers in Immunology, 2024)
Pancreatic inflammation is a risk factor for the development of pancreatic cancer. Increased presence of inflammatory macrophages can be found in response to a KRAS mutation in acinar cells or in response to experimentally-induced pancreatitis. Inflammatory macrophages induce pancreatic acinar cells to undergo dedifferentiation to a duct-like progenitor stage, a process called acinar-to-ductal metaplasia (ADM). Occurrence of ADM lesions are believed to be the initiating event in tumorigenesis. Here we will discuss how macrophage-induced oxidative stress contributes to ADM and how ADM cells shape the fibrotic stroma needed for further progression.